The Benefit of Cupping (Hijamah) to Post-Vaccination Mental & Physical Health - Abu Zahrin, Syaidatun Nazirah; Mohamad Said, Mohamad Mohsin; Mohd Iskandar Sandakumaran, Amirah Izzati; Zubair Khan, Asiah Sofiyyah Khan (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2021)
The Muslims have been challenged significantly during the pandemic, both mentally and physically. Staying safe and healthy have been a great concern of all throughout the world. The prophetic ways of life have been fundamental examples in how we could go about in dealing with the disastrous effects of the pandemic, and also the AEFI (Adverse Effect Following Immunizations) that could affect some individuals in various ways. The purpose of this study is to promote the benefits of cupping (hijamah) as one of the ways in dealing with the AEFI that may cause blockage in the brain, heart attacks and sudden death. Cupping therapy (CT) is used in Asia, Europe, and the Middle East and is prevalent in Muslim communities where it is a recommended sunnah of the Prophet Muhammad PBUH. Cupping has been studied tremendously and proven to improve one’s health conditions related to high blood pressure, diabetes, high cholesterols, knee and joint pains, asthma, acne, migraine, respiratory problems and other medical issues. Cupping is also proven to be able to help improve one’s mental and physical health when affected by COVID- 19 or other diseases that increase dramatically during this pandemic. Finally, some challenges and their implications are discussed with recommendations.